Monopole harmonics for a special gauge - Zenaida E. S. Uy (International Journal of Mathematics and Mathematical Sciences, 1978)
The monopole harmonics for a special gauge are derived and found to differ from the Wu-Yang monopole harmonics by a factor of eiqγcosθ, where γ is a real parameter.